ExplanationWe know that, \((x + y)(x - y) = x^2 - y^2\)

So we can rewrite the:

\((x + 2y)(x - 2y) = x^2 - 4y^2 = 4\)

They can quickly compare 4 to 8 and determine B is greater.

If you forget the classic quadratic form, simply perform (first, outer, inner, last):

(x + 2y)(x - 2y) → \(x^2 - 2xy + 2xy - 4y^2 = 4\) → \(x^2 - 4y^2 = 4\)

Compare the quantities: Quantity A: 4 Quantity B: 8

Hence option B is correct.
_________________

Sandy

If you found this post useful, please let me know by pressing the Kudos Button

Try our free Online GRE Test